Scalability of Adaptation strategies to drought stress: the case of drought tolerant maize varieties in Kenya - Franklin Simtowe; Dan Makumbi; Mosisa Worku; Harriet Mawia; Dil Bahadur Rahut (International Journal of Agricultural Sustainability, 2021)
Droughts have devastating effects on agricultural productivity and livelihoods, which triggers a quest for adaptation strategies such as the development and deployment of drought tolerant maize varieties (DTMVs). This study examines the scalability of DTMVs in Kenya using household survey data from eight counties. Results show that the 2018 DTMV adoption rate of 26% could be doubled to 52% as farmer knowledge constraints are alleviated, could potentially be further increased to 56% if seed access constraints are addressed, and even rise to 60% if seed affordability constraints are lifted. There is heterogeneity in scalability across counties attributable to differences in levels of scaling efforts. The use of electronic media appears to be a key success factor to create awareness about DTMVs but could exclude more marginalized households and communities, which highlights the need for multipronged awareness strategies. Scalability calls for public-private partnerships to foster a sustained supply of seed to the farming communities at competitive prices.